An Afrocentric Reflection on the Prospects and Limits of Economic Sanctions in Africa: The Case Studies of Zimbabwe and Libya - Shai, Kgothatso; Legodi, Lebogang; Darboe, Mustapha; Ly Touray, Binta Ly Touray (African Journal of Sociological and Psychological Studies, 2022)
There is a wide body of academic literature on economic sanctions, which have become one of the key tools of international relations between the developing and industrialised states. What emerges from this literature is that the use, efficiency and limits of economic sanctions is not uniformly understood within the academic and diplomatic circles. The competing accounts on this subject cannot be delinked from the varying ideological interests of the states who impose economic sanctions and those who are targeted. In the ideational space, much of the literature in this regard is also based on Westernised perspectives and critics, which do not necessarily capture the essence of African reality. As such, this paper adopts Afrocentricity as a theoretical and contextual lens to reflect on the prospects and limits of economic sanctions in Africa. Due to the mosaic nature of Africa, this paper employs Zimbabwe and Libya as case studies in order to paint a qualitatively rich picture of the phenomena being studied under a context of limited respondents. The major revelation of this paper is that economic sanctions have short term achievements in terms of the change of deviant behaviour in the international system. With Zimbabwe and Libya cases, in the long run, however, economic sanctions have a potential to also harm the same segment of the population that is theoretically meant to benefit from them.